2018
DOI: 10.15406/ijawb.2018.03.00045
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the West African Black-Crowned Crane Balearica pavonina pavonina (Linn 1758) in the Sudano-Sahelian Wetlands of Northern Nigeria

Abstract: Scientific classification and conservation status Common name: West African black-crowned crane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Similarly, Hiragi et al (2014) described vertebral formula in Red-Crowned and hooded Crane. Edet et al (2018), reported on the conservation status of the Cranes in the wetlands of Northern Nigeria. However, to the best of our knowledge, little is known about of the gross morphology of the skeleton of the West African black-crowned crane.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hiragi et al (2014) described vertebral formula in Red-Crowned and hooded Crane. Edet et al (2018), reported on the conservation status of the Cranes in the wetlands of Northern Nigeria. However, to the best of our knowledge, little is known about of the gross morphology of the skeleton of the West African black-crowned crane.…”
Section: Introductionmentioning
confidence: 99%